Kaiso (ZBTB33) subcellular partitioning functionally links LC3A/B, the tumor microenvironment, and breast cancer survival - Sandeep K. Singhal; Jung S. Byun; Samson Park; Tingfen Yan; Ryan Yancey; Ambar Caban; Sara Gil Hernandez; Stephen M. Hewitt; Heike Boisvert; Stephanie Hennek; Mark Bobrow; Md Shakir Uddin Ahmed; et al. (Communications Biology, 2021)
Through automated image analysis, Singhal et al quantify nuclear versus cytoplasmic distribution of the Kaiso transcription factor in breast cancer patient tissue. They find that Kaiso distribution correlates with breast cancer subtype and overall survival, and discover a link between cytoplasmic Kaiso and autophagy marker LC3.